ZnIn2S4 with a hybrid reaction mechanism and sulfur vacancies for sustainable sodium storage - Yu Wang; He He Zhang; Zi Wen; Chang Ning Sun; Guo Yong Wang; Ming‐Sheng Wang; Chun Cheng Yang; Qing Jiang (Carbon Energy)
Abstract Conventional monometallic sulfides are usually conversion or conversion‐alloying‐dominated anodes, while the sluggish kinetics and severe volume variation greatly hamper their electrochemical properties in sodium‐ion batteries. Herein, bimetallic sulfides (Vs‐ZnIn2S4) are developed with S vacancies, which are verified via electron paramagnetic resonance. A possible reaction mechanism (intercalation–conversion–alloying) is proposed, which is characterized by in situ X‐ray diffraction. In addition, the small volume change during (de)sodiation of Vs‐ZnIn2S4 is also observed by in situ transmission electron microscopy. The Vs‐ZnIn2S4 anode shows ultrastable and superfast sodium storage performance, such as outstanding long‐term cycling durability at 10 A g−1 (349.6 mAh g−1 after 2000 cycles) and rate property at 80 A g−1 (222.7 mAh g−1). Moreover, the full cell [Vs‐ZnIn2S4//Na3V2(PO4)3/C] achieves an excellent property after 300 cycles (185.9 mAh g−1) at 5 A g−1, showing significant potential for real‐world applications.